A Contraction Fixed Point Theorem in Partially Ordered Metric Spaces and Application to Fractional Differential Equations - Xiangbing Zhou; Wenquan Wu; Hongjiang Ma (Abstract and Applied Analysis)
We generalize a fixed point theorem in partially ordered complete metric spaces in the study of A. Amini-Harandi and H. Emami (2010). We also give an application on the existence and uniqueness of the positive solution of a multipoint boundary value problem with fractional derivatives.